A new fluid scheme for weakly collisional plasmas: 1. General theory - Chiuderi, C.; Pietrini, P.; Torricelli-Ciamponi, G. (Journal of Geophysical Research: Space Physics, 2011)
We present a new approach to the study of two‐fluid hydrodynamics of weakly collisional plasma systems, such as those frequently encountered in the astrophysical context. Our starting point is the novel procedure developed in past years by Chen, Rao, and Spiegel (CRS) for the fluid description of semicollisional neutral monoatomic gases. The new system of fluid equations that include viscous and conductive effects has been successfully tested. However, the extension of such a procedure to plasmas is not a straightforward one. We have to deal with (at least) two components, with vastly different values of the masses, and the nature of collisions between charged particles is substantially different from the neutral particle case. We perform a preliminary careful examination of the basic requirements of the CRS method and identify the conditions under which an extension of such method is indeed possible. We then derive the system of fluid equations appropriate to the description of a weakly collisional two‐component plasma in the new scheme and discuss the differences with respect to the more familiar Navier‐Stokes approach. This paper is therefore of a general theoretical nature. However, we also point out that solar wind is a good testing ground for the newly derived system of fluid equations. This application will be the subject of a subsequent paper. Key Points New approach to two‐fluid hydrodynamics of weakly collisional plasmas